2006
DOI: 10.1167/iovs.06-0382
|View full text |Cite
|
Sign up to set email alerts
|

Differential Changes of Magnocellular and Parvocellular Visual Function in Early- and Late-Onset Strabismic Amblyopia

Abstract: PURPOSE.Studies in nonhuman primates show that monocular visual deprivation starting at different ages has different effects on cells in the parvocellular and magnocellular laminae of the lateral geniculate nucleus. The present study used color and luminance contrast sensitivity (CS) measurements to look for differences in parvocellular-and magnocellular-related visual function in human subjects with strabismic amblyopia. METHODS. Fifteen subjects with early-and 14 with late-onset strabismic amblyopia and simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 22 publications
(25 reference statements)
1
29
0
2
Order By: Relevance
“…Recently, an increasing number of studies have shown impairment in early-stage processing of visual information. This impairment is not only related to retina and eye diseases like glaucoma [17,21,[31][32][33] ambliopia and strabismus [34], melanoma-associated retinopathy [24,18,28], X-linked retinitis pigmentosa [26,35], congenital stationary night blindness [28], and neurological diseases as migraine [30] or Duchenne Muscular Dystrophy [29], but also to the neurocognitive or high-level of cortex processing disorders, such as schizophrenia [36,37], autism [38][39][40], working memory impairment [41] and dyslexia [25,[42][43][44][45].…”
Section: Selectivity To MC and Pc Pathwaysmentioning
confidence: 99%
“…Recently, an increasing number of studies have shown impairment in early-stage processing of visual information. This impairment is not only related to retina and eye diseases like glaucoma [17,21,[31][32][33] ambliopia and strabismus [34], melanoma-associated retinopathy [24,18,28], X-linked retinitis pigmentosa [26,35], congenital stationary night blindness [28], and neurological diseases as migraine [30] or Duchenne Muscular Dystrophy [29], but also to the neurocognitive or high-level of cortex processing disorders, such as schizophrenia [36,37], autism [38][39][40], working memory impairment [41] and dyslexia [25,[42][43][44][45].…”
Section: Selectivity To MC and Pc Pathwaysmentioning
confidence: 99%
“…Although anatomic anomalies of visual pathways in amblyopia are well known, 9 the results of studies in which authors evaluated concomitant retinal involvement remain controversial. [10][11][12][13][14][15][16] Some investigators have found an increased retinal nerve fiber layer thickness (RNFLT) 10,12 in amblyopic eyes, whereas others have found no significant differences.…”
mentioning
confidence: 99%
“…It has been documented that morphologic changes occurring during the late sensitive period selectively affect cells of the parvocellular pathway (17,21,(69)(70)(71) . It seems reasonable to re commend that treatment for amblyopia should be individualized, as some children with amblyopia may not respond to occlusion because of morphophysiologic dissociation between the magno-and parvocellular pathways (72) . (40) Reduces binocular function (32) , changes family routine (49) , may induce psychological problems (32) .…”
Section: Final Remarksmentioning
confidence: 99%